Situational activity on children’s leadership behaviours - Wong, Janelle (2019)
This qualitative research study aims to gain an insight into the leadership behaviours of children. Leadership development starts from young. Humans are social beings and we grew up gaining social skills interacting and communicating with people around us. Therefore, development of leadership should be built on continuously throughout one’s life because our social experiences begin from birth (Murphy & Reichard, 2011). This study was conducted in a day-care with a situational activity designed and conducted to observe children’s leadership behaviours through children’s social and emotional reactions. A total of nine children between the ages of three to six years old were involved in the study. The data was collected using digital video recordings and was analysed using theory-driven video analysis of episodes. The findings in the study indicate the coexistence of social and emotional skills through children’s leadership behaviours. Social and emotional skills in leadership is universal to both children and adult, only in different contexts. Twelve episodes of interactions have been identified and categorised into social capabilities and emotional intelligence. Each category illustrates the different leadership behaviours children display through their social capabilities and emotional intelligence in a mixed-age activity. This research provided an initial understanding of children’s leadership behaviours and more research needs to be done to further develop leadership development in early childhood education.